WAYS OF IMPROVING INCLUSIVE EDUCATION FROM LEGAL AND METHODOLOGICAL PERSPECTIVES (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This article explores the ways of improving inclusive education from both legal and methodological perspectives. Inclusive education is a key factor in ensuring equal rights, opportunities, and access to quality education for children with special needs. The study emphasizes the importance of legal frameworks that guarantee inclusion and protect the rights of learners, as well as methodological approaches that enable effective teaching and learning in diverse classrooms. International conventions, national legislation, and policy reforms are analyzed as legal instruments for supporting inclusion, while methodological perspectives focus on teacher training, curriculum adaptation, individualized learning strategies, and the use of assistive technologies. The research highlights the challenges faced in implementing inclusive practices, such as insufficient awareness, limited resources, and lack of qualified staff, and suggests comprehensive solutions aimed at building sustainable systems. The findings underline that strengthening the legal base and enhancing methodological practices can significantly improve the inclusivity of education and promote the academic, social, and emotional development of all learners.